Expenditure Patterns of Migrant Households: Evidence from Moldova - Robert Poppe (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
This paper examines the effect of temporary and permanent migration on household expenditures and on asset/durables ownership. Using household survey data from Moldova, this paper relies on the matching approach for identification. It is shown that temporary migrant and permanent migrant households have additional expenditures for food compared to non-migrant households. Concerning the ownership of goods or assets compared to the regional crisis in 1998, temporary and permanent migrant households are more likely to own more goods or assets than non-migrant households. Migration has stronger effects on ownership in rural areas. Overall, the findings indicate that temporary migration has a stronger effect on household expenditures than permanent migration.
Keywords: 330; Expenditures; Remittances; Migration; Propensity Score Matching